Analisa Kinerja Saluran Primer Daerah Irigasi Way Geren Kecamatan Lolong Guba Kabupaten Buru, Provinsi Maluku - Sangkala, Sofyan; Nara, Obednego Dominggus; Titaley, Henriette Dorothy (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The evaluation of irrigation network performance is essential to ascertain the status of these networks. This is governed by the Regulation of the Minister of PUPR No.12/PRT/M/2015 about the Exploitation and Maintenance of Irrigation Networks. This study aims to assess the physical condition of the principal channel, its performance, and the availability of discharge. The physical condition and functionality of the Way Geren irrigation canal remain satisfactory. Channels 1 and 2 achieved an 89% presentation and a 77% capacity for discharge. The embankment height was sufficient to prevent runoff at 85% for both measurements. However, the implementation of repairs and maintenance received a presentation score of only 30% due to the lack of maintenance and repairs conducted on the channel. The performance evaluation of primary irrigation canals in the Way Geren irrigation region indicates a 67.5% rating of mediocre condition, necessitating maintenance of a reparative nature. This enhancement aims to rehabilitate the principal irrigation canal of the Way Geren irrigation region to improve its operational efficacy. Based on the Network Scheme for an area of 453 hectares, with a designated discharge (Q) of 0.802 m³/sec, a wet cross-sectional area (A) of 0.863 m², a flow velocity (V) of 0.158 m/s, and a flowing discharge (Q) of 0.136 m³/sec at a door opening of 0.09 m.